Smart Reconfigurable Antennas for IoT Applications - T. Rama Krishna (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This research examines the design and efficacy of a frequency-reconfigurable antenna for Internet of Things (IoT) applications. The antenna is designed to function across many frequency bands and is reconfigurable to accommodate diverse communication standards and environmental circumstances. The antenna design comprises a monopole with a single PIN diode and a 50Ω feed line. The diode’s state alteration enables the antenna to be adjusted for dual-band and wideband operation. The antenna’s performance was assessed using simulation. The antenna exhibited effective impedance matching, satisfactory gain, and consistent emission patterns across many frequency bands. The antenna has modest dimensions of 26 mm by 19 mm by 1.6 mm. The frequency range is from 2.95 GHz to 8.2 GHz, whilst the dual-band mode encompasses 2.7-3.8 GHz and 4.57-7.4 GHz. The maximum gain is 1.57 dBi for the wideband mode exhibiting an omnidirectional radiation pattern. The maximum gain of the dual-band mode is 0.87 dBi at 3 GHz and 0.47 dBi at 6 GHz, exhibiting an omnidirectional radiation pattern.